A cow can change everything—Heifer International - East Africa Dairy Development Project (East Africa Dairy Development Project, 2010)
Through their East Africa Dairy Development project (EADD), Heifer International is providing farmers with training and support to help them double their dairy-related incomes over the next 10 years.